Switchable nonlinear absorption and ultrafast dynamics process of Nb2CTx. Issue 1 (10th September 2021) - Chen, Chen; Zhang, Jianfeng; Li, Qiang; Hong, Gang; Lin, Chun; Wang, Qiang
Abstract: The nonlinear absorption of two-dimensional (2 D) Nb2CTx (MXene) nanosheets were investigated by using nanosecond Z-scan measurements in 532 nm under different laser intensities. It was found that, Nb2CTx nanosheets exhibit from saturable absorption (SA) to reverse saturable absorption (RSA). With the increase of incident intensity, a switch from SA to RSA occurs under some excitation intensities. Besides, ultrafast carrier dynamics of Nb2CTx nanosheets were also investigated by using pump-probe technique. It was found that the relaxation contains a biexponential decay process with two decay components, a fast and a slow one. The investigations show that Nb2CTx nanosheets can be used as building ultrashort pulse generation and optoelectronic devices.